COMPLEXIFICATION IN RUSSIA'S LEGAL EDUCATION: CLASSICAL APPROACH AND INNOVATIONS - S. Smirnova (Теория и практика судебной экспертизы)
The paper examines the issue of improving legal education in the country by means of transforming methodological approaches to the educational process on the basis of complexification.